Upaya Peningkatan Pengetahuan dan Pencegahan Komplikasi Kehamilan di Masyarakat - Priasmoro, Dian Pitaloka; Sunarmi; Roesardhyati, Ratna; Adelia, Nony; Candra W, Dicky (Yayasan Inspirasi El Burhani, 2025)
Introduction: Undetected or poorly managed pregnancy complications can lead to maternal and infant mortality. One form of intervention that can be done is through counseling in the form of routine pregnant women's classes. In this class, pregnant women can be given more in-depth information about healthy pregnancy, signs of complications, and how to prevent complications that can occur. Objective: The purpose of this community service is to provide education about pregnancy and prevent complications during pregnancy. The number of participants is 10 people who meet the criteria. Method: This community service activity used a lecture and practice approach. Program evaluation was carried out through pre and post tests to measure maternal knowledge. Result: The results of this community service activity showed that almost all participants increased their knowledge and awareness of pregnancy check-ups, pregnant women also understood about pregnancy risks and early detection that can be done one of them through pregnancy gymnastics activities. Conclusion: Similar activities need to be improved throughout the Puskesmas area, because this prevention action is considered very effective for detecting pregnancy risks and preventing complications during pregnancy.